Dermofat grafts to the extraconal orbital space. - Rose, G E (1992)
Dermofat grafts were placed in the upper or lower lid sulci in 35 subjects, aged from 11 to 59 years, to improve the cosmesis of volume deficient sockets or prevent tissue adhesion. Volume enhancement and cosmetic improvement were achieved in 31 patients, in whom useful vision was present in 13/22 after previous trauma, in 4/4 with facial clefting, and in 3/3 with orbital or facial fat atrophy. Grafts were used successfully in nine patients to prevent scar formation after division of adhesions between the eyelids or levator muscle and the orbital margins. A reduction of the bulk of upper-lid grafts was required in three cases; histopathology of the excised fat showed relatively minor degrees of inflammation, atrophy, and fibrosis.